2021
DOI: 10.1111/jfpp.15725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide fumigation on microorganisms and quality of dried apricots during storage

Abstract: Apricot (Prunus armeniaca L.) is a nutrient-rich edible drupe, which is classified under the Prunus species of Prunoidae and has beneficial properties in nutrition and health care (Hacıseferoğulları et al., 2007).China is one of the four major apricot-producing countries in the world, along with the United States, Australia, and Turkey (Toğrul & Pehlivan, 2003). However, the harvesting of ripe fresh apricots is usually done during the hot season, which can lead to fruit decay, softening, browning, and pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…As one of the most significant pathogens, A. niger severely influences the quality and marketing value of jujubes. Chen et al found that A. niger, which has the highest pathogenicity and isolation frequency, is one of the main pathogens causing jujube mildew and rot in Xinjiang, China [12]. Zhang et al investigated the main fungal diseases of Zizyphus mauritiana Lam in the Yunnan Province of China, and found that the pathogenic fungi of jujubes involved nine genera, among which A. niger was a common one [13].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most significant pathogens, A. niger severely influences the quality and marketing value of jujubes. Chen et al found that A. niger, which has the highest pathogenicity and isolation frequency, is one of the main pathogens causing jujube mildew and rot in Xinjiang, China [12]. Zhang et al investigated the main fungal diseases of Zizyphus mauritiana Lam in the Yunnan Province of China, and found that the pathogenic fungi of jujubes involved nine genera, among which A. niger was a common one [13].…”
Section: Introductionmentioning
confidence: 99%